1153 Association Of Nocturnal Sleep Disturbance And Prospective Cognitive Decline In Cognitive Normal Elderly: Findings From The National Alzheimer's Coordinating Center Uniform Dataset. (27th May 2020) - Bubu, O M; Mbah, A K; Williams, N J; Turner, A D; Parekh, A; Mullins, A E; Kam, K; Umasabor-Bubu, O Q; Varga, A W; Rapoport, D M; Ayappa, I; Jean-Louis, G; et al.
Abstract: Introduction: We determined whether nocturnal sleep disturbance (NSD) is associated with prospective cognitive decline in clinically normal older adults Methods: Prospective longitudinal study utilizing data from the National Alzheimer's Coordinating Center (NACC) Uniform Data set (UDS). NSD data, as characterized by the Neuropsychiatric Inventory Questionnaire (NPI-Q), were derived from 10, 600 participants at baseline, with at least one UDS follow-up visit, from 32 National Institute of Aging Alzheimer's Disease Research Centers (ADRC). Prospective cognitive decline was characterized as incident mild cognitive impairment (MCI) diagnosis during UDS follow-up. Logistic mixed-effects model with random intercept and slope examined associations between the NSD and longitudinal cognitive decline. All models included age at baseline, sex, years of education, APOE ε4 status and their interactions with time. Time was operationalized as years from baseline for each participant. Results: Of the 10, 600 cognitively normal participants at baseline, 1, 017 (8.6%) had NSD. The proportion of males versus females with sleep problems was 10.1% vs. 9.3% respectively. For participants with NSD and no NSD, the mean (SD) age was 71 (7.3) and 70 (5.7) years and average follow-up time was 5.2 (2.6) and 4.9 (2.7) years, respectively. Participants with NSD were significantly more likely to develop incident MCI during UDS follow-up (OR: 1.42, p =.003). The interaction of NSD with time was significant ( p < .001) suggesting an increase in the likelihood of conversion to MCI increased over time. Furthermore, there were significant differences in mean conversion rates to MCI in the NSD group when the previous time-point was compared to the next ( p <01), with a time dependent dose response in the risk of conversion to MCI observed. Conclusion: In elderly cognitive-normal individuals, nocturnal sleep disturbance is associated with a time-dependent progression risk to MCI. These findings are consistent with the role of disturbed sleep in the development of Alzheimer's Disease. Support: NIH/NIA/NHLBI (L30-AG064670, CIRAD P30AG059303 Pilot, T32HL129953, R01HL118624, R21AG049348, R21AG055002, R01AG056031, R01AG022374, R21AG059179, R01AG056682, R01AG056531, K07AG05268503, K23HL125939)